Initiating Opioid Agonist Treatment for Opioid use Disorder Nationally in the Veterans Health Administration: Who Gets What?. Issue 1 (January 2020) - Manhapra, Ajay; Stefanovics, Elina; Rosenheck, Robert
Background: Despite substantial benefits associated with opioid agonist treatment (OAT) with buprenorphine and methadone for opioid use disorder (OUD), only a small proportion of patients with OUD initiate OAT. There is a lack of studies addressing the correlates of OAT initiation among patients with OUD. Methods: Using Veterans Health Administration (VHA) national administrative data, we identified veterans with OUD who started OAT with either buprenorphine or methadone maintenance treatment (MMT) in fiscal year (FY) 2012 (first prescription of buprenorphine or first methadone clinic visit after the first 60 days of FY) and those who received no OAT that year. Multivariate logistic regression models including sociodemographic characteristics, diagnoses, and service and psychotropic drug use variables were used to identify independent predictors of OAT initiation. Results: Greater age (10-year increments; odds ratio [OR]: 0.96, 95% confidence interval [CI]: 0.0.9–0.97) and black race (OR: 0.46, 95% CI: 0.38–0.55) were associated with lower odds of being started on buprenorphine compared with no OAT, but not with MMT initiation. Veterans with cocaine and anxiolytic-sedative hypnotic use disorders had higher odds of being started on both buprenorphine and methadone compared with no OAT. Receipt of any mental health inpatient treatment was associated with higher odds of being started on buprenorphine but not methadone. Overall, we were unable to identify a robust set of patient characteristics associated with initiation of OAT. Conclusion: This study points out the stark reality that in the middle of an opioid crisis, we have very little insight into which patients with OUD initiate OAT.